ANALYSIS OF SHIP AGENCY SERVICE BUSINESS COMPETITIONIN SUPPORTING NATIONAL SEA TRANSPORTATION ACTIVITIESAT BANTEN PORT - TDAHJONO, SH., MH, Dr. EKA BUDI; Sibarani, Mauritz H.M; Kasiono, Roy (Meteor STIP Marunda, 2023)
Banten Province has three major ports, namely Cigading Port (CDG), Ciwandan Port (CDW), and Merak Mas Port (MN), which serve as the backbone of national sea transportation in the western Java region. The enactment of Law No. 17 of 2008 on Shipping has separated the regulatory and operational functions of ports, creating opportunities for both state-owned and private enterprises to compete in ship agency services. This study aims to analyze the competitive landscape of ship agency services at Banten ports in supporting national sea transportation activities. A qualitative research methodology was employed, utilizing observation, interviews, and documentary analysis as data collection techniques. The GE-McKinsey Matrix was applied to evaluate industry attractiveness and business strength across the three ports. The findings reveal that CDG Port occupies a HIGH–HIGH position in the GE Matrix with an Industry Attractiveness Index of 95.0 and a Business Strength Index of 80.0, indicating a dominant competitive position. CDW Port is positioned at HIGH–MEDIUM (IA: 57.5, BS: 75.0), while MN Port occupies a LOW–LOW position (IA: 17.5, BS: 20.0). These results indicate that ship agency services at Banten ports exhibit significant competitive disparity, influenced by factors such as market share, facilities, location, brand recognition, and regulatory environment. Strategic recommendations are provided for each port to enhance their respective competitive positions in supporting national sea transportation.